VD_FINDINFO LAVAM 5/12 - 11/2012 vom 25. April 2012 - VD Tribunal cantonal (2012)
PROCÈS DEVENU SANS OBJET, DÉPENS, RADIATION DU RÔLE | 30 al. 1 LPA-VD, 55 al. 1 LPA-VD, 83 LPA-VD, 91 LPA-VD, 94 al. 1 let. c LPA-VD, 99 LPA-VD